2020
DOI: 10.1152/ajprenal.00332.2019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acute moderate- to high-intensity aerobic exercise on markers of immune function and microparticles in renal transplant recipients

Abstract: Renal transplant recipients (RTRs) and patients with nondialysis chronic kidney disease display elevated circulating microparticle (MP) counts, while RTRs display immunosuppression-induced infection susceptibility. The impact of aerobic exercise on circulating immune cells and MPs is unknown in RTRs. Fifteen RTRs [age: 52.8 ± 14.5 yr, estimated glomerular filtration rate (eGFR): 51.7 ± 19.8 mL·min−1·1.73 m−2 (mean ± SD)] and 16 patients with nondialysis chronic kidney disease (age: 54.8 ± 16.3 yr, eGFR: 61.9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This is the first study to evaluate the role of intradialytic exercise on CCR5+ leukocytes. Previously, Highton et al 13 demonstrated that a single bout of endurance exercise lowered CD14+CD16+ intermediate monocytes in the peripheral blood of CKD patients, which suggests an anti-inflammatory effect. In this sense, the maintenance of CD14+CCR5+ proportions at a stable value in our study may be due to the decreases in intermediate monocytes induced by exercise.…”
Section: Discussionmentioning
confidence: 94%
“…This is the first study to evaluate the role of intradialytic exercise on CCR5+ leukocytes. Previously, Highton et al 13 demonstrated that a single bout of endurance exercise lowered CD14+CD16+ intermediate monocytes in the peripheral blood of CKD patients, which suggests an anti-inflammatory effect. In this sense, the maintenance of CD14+CCR5+ proportions at a stable value in our study may be due to the decreases in intermediate monocytes induced by exercise.…”
Section: Discussionmentioning
confidence: 94%
“…1 ) (CV 13.88%). This methodology and gating strategy was adapted from previous research from our group (Martin et al 2018 ) and has been used previously in the general population (Highton et al 2019 ) and in those with chronic kidney disease (Highton et al 2020 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Both acute aerobic exercise and regular aerobic exercise training can promote favourable changes in MPs (i.e. reduced total and TF + MP concentration) (Babbitt et al 2013 ; Highton et al 2019 ), an effect which has also been observed in chronic kidney disease and renal transplantation (Highton et al 2020 ). In addition, regular aerobic exercise training can reduce circulating pro-inflammatory cytokine and chemokine concentrations (Gleeson et al 2011 ; Trøseid et al 2004 ), and therefore, may be therapeutic for HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…These differences between groups reverted to normal one-day post-exercise; it was postulated that the effects might be related to the immunosuppressive medication. Highton et al [ 235 ] found no differences in changes of classical, intermediate, and non-classical monocyte subset proportions, nor the percentage of platelet-derived microparticles that expressed tissue factor (TF+), between groups of non-dialysis patients, healthy controls, and KTRs. As such, moderate exercise did not cause aberrant immune cell activation, supporting its safety from an immunological standpoint.…”
Section: Transplantationmentioning
confidence: 99%
“…Two studies explicitly stated that no adverse events occurred as part of the intervention [ 212 , 213 ]. O’Connor et al [ 235 ] reported that, from baseline until 12-months (i.e. encompassing the exercise period reported in Greenwood et al [ 212 ]), 15.4% of patients in the exercise groups were hospitalised, this was compared to 40% of patients in the control arm.…”
Section: Transplantationmentioning
confidence: 99%